2019
DOI: 10.1364/oe.27.027256
|View full text |Cite
|
Sign up to set email alerts
|

Passively mode-locked semiconductor quantum dot on silicon laser with 400 Hz RF line width

Abstract: Mode-locked InAs/InGaAs quantum dot lasers emitting optical frequency combs centered at 1310 nm are promising sources for high-speed and high-capacity communication applications. We report on the stable optical pulse train generation by a monolithic passively mode-locked edge-emitting two-section quantum dot laser based on a five-stack InAs/InGaAs dots-in-a-well structure directly grown on an on-axis (001) silicon substrate by solid-source molecular beam epitaxy. Optical pulses as short as 1.7 ps at a pulse re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…For passively mode-locked semiconductor lasers, the RF linewidth of the repetition frequency signal is in most cases dominated by the ASE-induced timing jitter of the pulse train. [52,[58][59][60][61][62] In this case the repetition frequency signal has a Lorentzian profile. However, if the Lorentzian linewidth becomes sufficiently narrow the RF linewidth can be dominated by environmental and technical noise resulting in a non-Lorentzian profile.…”
Section: Single Sideband Phase Noise Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…For passively mode-locked semiconductor lasers, the RF linewidth of the repetition frequency signal is in most cases dominated by the ASE-induced timing jitter of the pulse train. [52,[58][59][60][61][62] In this case the repetition frequency signal has a Lorentzian profile. However, if the Lorentzian linewidth becomes sufficiently narrow the RF linewidth can be dominated by environmental and technical noise resulting in a non-Lorentzian profile.…”
Section: Single Sideband Phase Noise Measurementmentioning
confidence: 99%
“…[ 39 ] To determine the RF linewidth achievable when eliminating technical and environmental noise, a SSB‐PN measurement can be performed. [ 59 ] Figure a shows the SSB‐PN of the repetition frequency signal (755 MHz) at sufficiently large offset frequencies from the carrier to avoid influence of technical noise. Together with the measured SSB‐PN, a Lorentzian profile with a 1 Hz FWHM is plotted.…”
Section: Single Sideband Phase Noise Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the solid-state waveguide lasers based on laser crystals, electrically pumped semiconductor laser diodes based on the III-V materials also receive wide applications in silicon photonics [91,[95][96][97][101][102][103][104][105][106][107][108][109]. The most commonly used SAs in III-V systems are InAs and InGaAs quantum-dot (QD) layers fabricated by molecular beam epitaxy (MBE).…”
Section: Mode-locked Waveguide Lasersmentioning
confidence: 99%
“…The active region is the unintentionally doped GaAs waveguide that sandwiched by p-and n-AlGaAs QD layers. More recently, Auth et al also demonstrated 9.4 GHz III-V laser based on a five-stack InAs/InGaAs QD layers [97]. The superb compatibility with the existing CMOS logic enables III-V laser systems to be an important platform for the generation of ultrashort pulses.…”
Section: Mode-locked Waveguide Lasersmentioning
confidence: 99%